Factors Affecting Women’s Participation in Household Decision-Making: Bago Region, Myanmar Rural Area - Zin, Htet Htet; Chamruspanth, Viyouth; Srisontisuk, Somsak (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2025)
The objectives of the study are 1) to analyze the women’s participation in household decision-making, and 2) to identify the factors affecting women’s participation in household decision-making in Myanmar’s rural area. The descriptive quantitative method has been applied to meet the objective of this study, and a structured questionnaire has been used for interviewing 355 rural women who received microfinance services from Early Dawn Microfinance, Myanmar. Simple random sampling method has been used to identify the number of respondents. According to the regression analysis of SPSS version 29.0, micro-credit (.126; p=0.002) and financial literacy (0.410; p=0.001) have significantly positive effect on women’s household decision-making. Additionally, studied women seem to have significant participation in decision-making in household economics, social and household affairs. However, women still have less decision-making participation in household maintenance, large purchases, and financial decision-making than other decision-making areas. It indicated that certain traditional attitudes towards gender role that hinders women’s full participation in some areas of household decisions. According to the study results, microfinance services especially micro-credit, financial literacy and gender equality are important strategies to enhance the participating of Myanmar rural women’s household decision-making.